(untitled) (IJM: Journal of Multidisiplinary, 2025)
The rapid development of financial technology (fintech) in Indonesia has brought significant changes to the landscape of financial services, particularly through the emergence of increasingly accessible digital credit services. One of the key innovations in this space is the Buy Now Pay Later (BNPL) scheme. Shopee PayLater (SPayLater) has emerged as one of the most favored BNPL services. However, several challenges cannot be overlooked. Issues such as consumer protection, cost transparency, and the risk of over-leverage have become major concerns in the dynamics of this service. The presence of the Financial Services Authority (Otoritas Jasa Keuangan/OJK) as a regulatory and supervisory body plays a crucial role. This study aims to thoroughly examine how OJK formulates and implements policies related to the security and sustainability of the Shopee PayLater service. It also explores the effectiveness of OJK's supervisory mechanisms and how they respond to the challenges arising from the growth of BNPL services. The scope of the discussion includes an analysis of the current regulations, an evaluation of the supervision systems in place, and the policy implications for the continually evolving digital credit ecosystem particularly in maintaining a balance between financial innovation and the protection of consumer rights.